PENGARUH KEAKTIFAN MAHASISWA DALAM BERORGANISASI TERHADAP KEDISIPLINAN BELAJAR MAHASISWA PAI UIN RADEN FATAH PALEMBANG - Muhammad Faisal Ma'ruf; Sofyan Sofyan; Husnah Lutfiah (PAI RAFAH, 2021)
Higher education is a place for students to learn to prepare for the future, within the college there is an organization which is one of the places for students to develop their potential. The title of this research is the Effect of Student Activity in Organizing Against the Learning Discipline of PAI UIN Raden Fatah Palembang Students. This study aims to find out: how active students are in organizing, how student learning discipline is and is there an influence of student activity in organizing student discipline in Islamic Education study programs. This research is descriptive in nature which means the researcher wants to describe or give an objective picture by giving questions to respondents so that they get the answers they need. This study uses a quantitative approach. The poulasi in this study were 2018 Islamic Religious Education students who were active in organizing. The analysis in this study using statistical figures and scores processed by the process of moving data into the form of distribution tables, then calculating the correlation index between the two variables with the product moment correlation technique. The results of this study indicate that the activeness of students in organizing into the medium frequency category with a percentage of 67.3%, while the discipline of learning into the medium frequency category with a percentage of 67.3%. Then the results of this research that the effect of student activeness in organizing learning discipline has a significant effect with a correlation coefficient of 0.623 and has a comparison value greater than the coefficient of the table (r table) that is equal to 0, 265 at a significant level of 5%.